Introduction - Joyce D. Stern (Journal of Research in Rural Education, 1992)
The three articles that follow attempt to determine certain considerations for gauging the effects of state and federal policies on rural schools. The focus is on rural America, but the concerns represented have been forged within a wider arena. For some time now the nation has held a sustained focus on education as the key to economic health and the ability to maintain its leadership in the world. This focus took on a new level of commitment and visibility when, in 1989, the President and the governors, in an unprecedented move, met at an education summit to agree upon a set of education goals for the nation. These goals affect everyone, from pre-school children to adults.